2019
DOI: 10.1177/1724600818814462
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of familial adenomatous polyposis in the southeast of Brazil: identification of six novel mutations

Abstract: Background: The goal of this study was to screen point mutations and deletions in APC and MUTYH genes in patients suspected of familial adenomatous polyposis (FAP) in a Brazilian cohort. Methods: We used high-resolution melting, Sanger direct sequencing and multiplex ligation-dependent probe association (MLPA) assays to identify point mutations, and large genomic variations within the coding regions of APC and MUTYH genes. Results: We identified 19 causative mutations in 40 Brazilian patients from 20 different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Phenotypic differences in FAP patients are not only influenced by the site of the APC genetic variant but also vary within a family. Araujo et al reported high intra‐familial diversity of extracolonic manifestations 41 . Meanwhile, in the current study, we investigated whether patients with a severe phenotype had family members with the same phenotype.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Phenotypic differences in FAP patients are not only influenced by the site of the APC genetic variant but also vary within a family. Araujo et al reported high intra‐familial diversity of extracolonic manifestations 41 . Meanwhile, in the current study, we investigated whether patients with a severe phenotype had family members with the same phenotype.…”
Section: Discussionmentioning
confidence: 85%
“…Araujo et al reported high intra‐familial diversity of extracolonic manifestations. 41 Meanwhile, in the current study, we investigated whether patients with a severe phenotype had family members with the same phenotype. The results showed high familial accumulation of an abundance of FGPs and duodenal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical phenotype of MUTYH -associated polyposis (MAP) is similar to AFAP. MAP has an autosomal recessive type of inheritance [8]. In this article, only FAP cases with allelic variants of the APC gene will be considered.…”
Section: Introductionmentioning
confidence: 99%